2019
DOI: 10.1177/2055207619897155
|View full text |Cite
|
Sign up to set email alerts
|

Minimum data set development for a drug poisoning registry system

Abstract: Objective: Drug poisoning is the most prevalent type of poisoning throughout the world that can occur intentional or unintentional. Standard way for data gathering with uniform definitions is a requirement for preventing, controlling and managing of drug poisoning management. The purpose of this study was to develop a minimum data set, as an initial step, for a drug poisoning registry system in Iran. Methods: This was descriptive and cross-sectional study that was performed in 2019. As the first step a compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…These centers provide specialized information to the public and medical staff. These toxicology information centers offer counseling for individuals who have been poisoned and provide education and research services for the prevention and treatment of poisoning [ 33 ]. However, based on the searches performed in scientific databases and the review of the systems used by the Ministries of Health of different countries, no coherent information management system was found that specifically covered corrosive ingestion and most of the systems included all poisonings [ 38 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These centers provide specialized information to the public and medical staff. These toxicology information centers offer counseling for individuals who have been poisoned and provide education and research services for the prevention and treatment of poisoning [ 33 ]. However, based on the searches performed in scientific databases and the review of the systems used by the Ministries of Health of different countries, no coherent information management system was found that specifically covered corrosive ingestion and most of the systems included all poisonings [ 38 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Registry systems typically use MDS to enable accurate data analysis, decision-making, and appropriate management of poisoning cases [ 32 ]. Using an MDS in a clinical registry system is critical to achieve consistent and comparable data on a specific disease or condition [ 33 ]. The MDS of corrosive ingestion is required for the ongoing collection and maintenance of the data and is the main requirement for implementing a registry and information system.…”
Section: Introductionmentioning
confidence: 99%
“…Disease registries are designed to collect and manage information about the approaches and outcomes of a population of patients to evaluate and improve care quality and safety, patient monitoring and follow-up, and facilitate new research (29). As an information manage-ment tool, the poisoning registry is an important source of information about poisoning patterns, decision-making, and healthcare provision (30). In registries, a minimum dataset (MDS) is usually utilized to facilitate the precise data analysis, decision-making, and management of disease cases (31).…”
Section: Introductionmentioning
confidence: 99%
“…Disease registration systems provide an important tool for public health surveillance (8). Electronic record of patient health information, while providing a dynamic and flexible structure for reporting (9,10), Allows the discovery of hidden knowledge from stored data. With the expansion of electronic data registration in the health care, there is a large and complex amount of data that cannot be analyzed by traditional methods.…”
Section: Introductionmentioning
confidence: 99%